China's maritime power and strategy history, national security and geopolitics - Ju, Hailong 1973- (World Scientific Publishing Co.Pte.Ltd., 2015)
This book conducts a comprehensive study on China's maritime strategy. It discusses the lessons of maritime power history that must be learnt by Chinese today, the relations between China's maritime strategy and domestic developing problems of China, the status and influence of maritime strategy from China's overall development strategy perspective, and the geopolitical targets of Chinese navy in 2050.China's maritime strategy is one of the most important academic and realistic subjects in the present and future. This book is the first book to discuss China's maritime strategy comprehensively in and outside China. It will give readers a better sense of why China has to develop its sea power, why it lays so much emphasis on Taiwan and the South China sea, why the country can make friends with India but not Japan, and why China's maritime strategy will never challenge America but has to face the pressure from America's maritime hegemony, and so on